Pengaruh Kepemimpinan Transformasional Terhadap Organizational Citizenship Behavior Yang Dimediasi Oleh Komitmen Organisasi Pada Kantor Badan Pusat Statistik Kota Medan - Amin, Qadar Al (Jurnal Ekonomi Bisnis Digital, 2022)
The results of this study indicate that Transformational Leadership has a positive and significant direct effect on Organizational Commitment. Transformational Leadership has a direct and significant negative effect on Organizational Citizenship Behaviour. Transformational Leadership has a negative effect on Organizational Citizenship Behaviour through organizational commitment. The results of the R2 value obtained by the coefficient of determination of 0.118, meaning that the effect of the variable Transformational Leadership on Organizational Commitment is 11.8% while the rest is influenced by other variables. The results of the coefficient of determination is 0.040, meaning that the influence of the variables of Transformational Leadership and Organizational Commitment on Organizational Citizenship Behaviour is 04.0% while the rest is influenced by other variables.